Peanut Allergy: An Overview - Al-Ahmed Nasser; Alsowaidi Shirina; Vadas Peter (Allergy, Asthma & Clinical Immunology, 2008)
Peanut allergies have been increasing in prevalence in most industrialized countries. Onset is typically in early childhood, with a trend towards earlier ages of presentation. The allergy is lifelong in most affected children, although 15-22% will outgrow their peanut allergy, usually before their teenage years. Manifestations of peanut allergy range from mild to severe, and risk factors predisposing to severe reactions are discussed. However, even in the absence of risk factors, peanut allergic individuals may still experience life-threatening anaphylactic reactions. Approaches to investigation and treatment, patterns of cross-reactivity and possible causes of rising prevalence are discussed.